Answer:
2a+ −11/2
Step-by-step explanation:
<em><u>Let's simplify step-by-step.</u></em>
1/4 (16a − 46) − (2a − 6)
<em>Distribute the Negative Sign:</em>
= 1/4 (16a − 46) + −1 (2a − 6)
= 1/4 (16a − 46) + −1 (2a) + (−1) (−6)
= 1/4 (16a − 46) + −2a + 6
<em>Distribute:</em>
= (1/4) (16a) + (1/4) (−46) + −2a + 6
=4a + −23/2 + −2a + 6
<em>Combine Like Terms:</em>
= 4a + −23/2 + −2a + 6
= (4a + −2a) + (−23/2 + 6)
= 2a + −11/2
<em>Answer:</em>
=2a + −11/2
hope this helps. p.s. i really need brainliest :)